Communication Beyond Words and Language: Role of Five Senses - Shankar Mishra, Amar (International Journal of Scientific Research and Management (IJSRM), 2023)
Communication has evolved and has been studied as the most important tool of interactions in personal as well as organisational life in the world. As we commonly understand communication as an interplay of words in a particular language, the present article attempts to answer the intriguing question about the origin of the communication and tries to understand its genesis at the metaphysical level. Words and language are representative of some inner thoughts and processes developed based on the perception created in human minds on the basis of what it perceives through sensory organs. The article highlights the role of five senses attributed to the human being in the communication that goes within the oneself. Author finds the root of the communication at ideation, thought and perception level by the interplay of various sense organs. Language oriented communication is just a minor dimension of the realm of communication that a human being experiences through eyes, ears, tongue, touch and nose. Further, author attempts to put the rationale that these five senses can’t communicate effectively when they perform their role in solos rather the interaction amongst them adds contours to the non-verbal expressions and same is manifested through different body languages.